Travesías para una romería: Sistematización de la vivencia en el XXV Festival de promeseros “Tibirita tierra de maravillas”, en los espacios académicos Danza Zona Andina, Teatro y Convivió 2022-2 (2024)
The main objective of this thesis is to systematize the creation process of the work “Travesías para una Romería”, considering the artistic-pedagogical principle of the experience of the Bachelor of Performing Arts (EAPEAT). The piece is inspired by the cultural expressions of the Tibirita Promeseros Festival, integrating ritual elements, dances and music into its narrative. The formulation of the problem highlights the need to strengthen cultural identity through artistic creation, using pedagogical processes that promote meaningful learning through direct experience.